ANALISIS KETERAMPILAN BERBICARA PADA MATERI DONGENG MELALUI DISKUSI KELOMPOK SISWA KELAS IV SDN DEPOKREJO - Hasan Ibnu Sani; Titi Anjarini; Suyoto (Jurnal Binagogik, 2024)
This research aims to determine speaking skills and to determine the internal and external factors of Depokrejo Elementary School students' speaking skills when learning Indonesian. The type of research used is descriptive qualitative. The subjects of this research consisted of 24 Depokrejo State Elementary School students for the 2022/2023 academic year. This research method is an analysis that refers to aspects of speaking skills such as fluency, intonation, expression, pronunciation and volume. Data collection techniques in this research used observation, tests, interviews and document study. The results of this research state that students' speaking fluency is good because their speaking skills use fairy tales to convey more than half of the contents of fairy tales. From the existing results, the aim is to find out internal factors such as language use, family, individual, as well as external factors such as the environment, students, and find out that there are 2 students in the very good category, 13 students in the good category, 4 students in the fair category, and those who need guidance are 5 students.